Enhancing Reading Comprehension By Using Aldiko Book Through Paraphrase Method - Sitti Aisa; Rustam Efendy Rasyid; Aswadi Aswadi; Suleha Ecca; Buhari Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
This research was use a quantitative and qualitative study, the research applied mixed method in the form of nonequivalent control group design because of there was possibility for the research to randomize the groups as the sample of This research. The reseacher devided the research object into two groups, experimental group who was given treatment, and the control group without treatment. This division was intended to test the hypotesis to know the condition after treatment. The pre-test will administratered students prior knowledge and the post-test will given to find out provement of the students reading comprehension using Aldiko book through paraphrase method. After giving the treatment, the researcher stated that the students in experimental group which were given treatment by using Aldiko Book as a media and paraphrase as method was effective in teaching reading than the students in control group by PDF Reader. The showed by the Mean score and standard Deviation of Students’ in Post-test score which is experimental with 20 sample had a mean score 65.25 and 11.64 higher then the control group 58.00 and 8.013. It means that there was a significance different between the experiental and control group